Quo vadis - Taylor, Robert, 1911-1969; Kerr, Deborah, 1921-2007; Ustinov, Peter; LeRoy, Mervyn, 1900-1987; Sienkiewicz, Henryk, 1846-1916 (MGM/UA Home Video, 1990)
The definitive version of the classic novel about ancient Rome during the reign of Nero.